Strengthening of local actors from a Local Productive Arrangement: a contribution to the agricultural sector - Uliser Vecino Rondon; Leonardo Cruz Cabrera; Adrián Cánova Herrandiz (Cooperativismo y Desarrollo, 2019)
The development of a country or territory is largely conditioned by its endogenous potential, as a key factor for development, related to innovation. Given these elements described, the objective of the study was to develop a Local Productive Arrangement procedure to strengthen local actors based on the improvement of the performance in the agricultural sector in La Isla de la Juventud. Methods of the theoretical and empirical levels were used, highlighting the techniques and instruments used such as scientific observation, interviews, surveys, the force field and the analysis of contents seen from the results of the organizational performance of the institutions within the Local Productive Arrangement. The proposal is an open system where internal and external factors converge as an integrated whole in order to provide efficient management of each actor under study. As fundamental results, it is highlighted that, not only is the objective fulfilled but it also contributes on the one hand that, the Local Productive Arrangement procedure constitutes a methodology that applied among local actors contributes to the effective articulation between them and to the improvement of the performance of the agricultural sector and, on the other hand, has an impact on the increase in production due to the development of new or improved products and services, and the satisfaction of the food needs of the population in the territory.